MATCHED MORALITY: AN ISLAMIC INTERPRETATION OF HAIKU POEMS - Mohd Nazri Latiff Azmi,; Isyaku Hassan,; Mohammad Talha Mohamed Idris, (2025)
Islam is often misconceived as incompatible with poetry, which hinders a deeper appreciation of poetry’s potential for expressing universal moral values. This book, Matched Morality: An Islamic Interpretation of Haiku Poetry, challenges this notion by revealing the hidden depths of traditional Japanese Haiku poetry from Islamic viewpoints. The book explores the ancient roots of Haiku in Japanese culture and its unique concurrence with Islamic morality. The authors demonstrate how the nature and philosophy of Haiku poetry reflect religious morality. The analysis focuses on how Haiku, with its concise poetic form and simple structure, can evoke powerful emotions and offer profound insights into the human condition. The book is more than just a literary interpretation; its line-by-line inductive analysis bridges cultural divides and draws inferences between Haiku’s themes of nature, reflection, and morality with core Islamic principles. Through careful examination of Quranic verses and Hadith, the authors of this book illustrate a shared pursuit of inner peace, social responsibility, and spiritual enlightenment in Islam and Haiku poetry. These new insights could enrich our understanding of Haiku poetry and Islam and offer a fresh perspective on the universal quest for morality in this ever-changing world. This book is valuable for academics, researchers, literature scholars, religious educationists and enthusiasts.